2015
DOI: 10.3346/jkms.2015.30.8.1017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect between Weight Perception and Comorbidities on Weight Control Behavior in Overweight and Obese Adults: Is There a Sex Difference?

Abstract: We investigated the interaction effect between body weight perception and chronic disease comorbidities on body weight control behavior in overweight/obese Korean adults. We analyzed data from 9,138 overweight/obese adults ≥20 yr of age from a nationally representative cross-sectional survey. Multiple logistic regression using an interaction model was performed to estimate the effect of chronic disease comorbidities on weight control behavior regarding weight perception. Adjusted odds ratios for weight control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
4
11
2
1
Order By: Relevance
“…However, we found no association between the type of NCD or the number of NCDs and the odds of engaging in weight control behaviour. This is similar to prior reports and echoes the importance of education on the association of weight and NCDs .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, we found no association between the type of NCD or the number of NCDs and the odds of engaging in weight control behaviour. This is similar to prior reports and echoes the importance of education on the association of weight and NCDs .…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, weight misperception conferred significantly lower odds of engaging in weight control behaviour. This corroborates evidence from other populations that an individual will not seek a solution (weight control) to a problem (overweight) they do not recognize exists (8,36,37). These results are also consistent with health behaviour theories that suggest that perceived susceptibility to a given condition is necessary to promote healthful behaviour change.…”
Section: Discussionsupporting
confidence: 87%
“…We found strong evidence for an association between perceived overweight and weight loss attempts from cross‐sectional studies. All included studies provided consistent evidence to suggest that individuals who perceived themselves as overweight had a higher likelihood of intending or attempting to lose weight than those who perceived themselves as normal weight (32 findings from high‐quality studies and 15 from low‐quality studies ). Overall, there was strong evidence to suggest that perceived overweight was associated with higher likelihood of trying to lose weight across all participant subgroups.…”
Section: Resultsmentioning
confidence: 88%
“…Initial database searches identified 10,398 unique records, and an additional 41 articles were identified by authors, from the reference lists of eligible articles or from supplementary searches. Full‐text review of 366 articles was completed, and 74 articles (indicated with asterisks in reference list) that described 78 studies were included in the review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to address weight status misperceptions, several studies have recommended increasing knowledge to properly self‐identify BMI‐based weight status . A large cohort study of adults examining changes in weight perceptions discussed the role of physicians in addressing inaccurate weight perceptions by discussing weight concerns with patients through strategies such as motivational interviewing .…”
Section: Introductionmentioning
confidence: 99%